In vitro propagation of Cyrtopodium saintlegerianum rchb. f. (orchidaceae), a native orchid of the Brazilian Savannah - Paiva Neto, Vespasiano Borges de; Rodrigues, Lennis Afraire; Boaretto, Amanda Galdi; Oliveira, Janaína Fernanda de; Torrezan, Mateus de Aguiar; Lima, Sebastião Ferreira de; Otoni, Wagner Campos (Crop Breeding and Applied Biotechnology, 2014)
In order to enable production of large quantities of plantlets for reintroduction programs, as well as economic exploration, Cyrtopodium saintlegerianum seeds were sown on Knudson culture medium. After seed germination, the protocorms were inoculated on Knudson culture medium supplemented with 6-benzyladenine (BA) and α-naphthaleneacetic acid (NAA). The obtained shoots were individually inoculated in Knudson supplemented with gibberellic acid (GA3) in order to promote elongation. Seedlings were evaluated and then transplanted into trays containing commercial substrate Plantmax^(r)-HT, or crushed Acuri leaf sheath. Auxin/cytokinin ratio influenced in vitro propagation of C. saintlegerianum, resulting in increased shoot number when 2.0 mg L^-1 BA was added to the culture medium in the absence or presence of 0.5 mg L^-1 NAA. This species proved to be promising for massal in vitro multiplication. Despite having incremented in vitro shoots elongation, the use of GA3 is unnecessary since it contributed negatively in the acclimatization of plants.

Visando à obtenção de grande quantidade de mudas para programas de reintrodução, bem como viabilizar sua exploração comercial, sementes de Cyrtopodium saintlegerianum foram incubadas em meio Knudson. Após a germinação, os protocormos foram inoculados em meio Knudson suplementado com 6-benzilaminopurina (BA) e ácido α-naftalenoacético (ANA) para indução de brotações, que foram posteriormente individualizadas e inoculadas em meio Knudson acrescido com ácido giberélico (AG3), para promover alongamento. As plantas resultantes do processo in vitro foram avaliadas e transplantadas para bandejas contendo Plantmax^(r) e casca de Acurí triturada. A relação auxina citocinina influencia na propagação in vitro de C. saintlegerianum, induzindo um incremento no número de brotações quando o meio de cultura foi acrescido de 2,0 mg L^-1 de BA, na ausência ou presença de 0,5 mg L^-1 de ANA. A espécie demonstrou-se promissora na multiplicação massal in vitro. O uso do ácido giberélico favoreceu o alongamento das brotações in vitro, mas contribuiu negativamente na aclimatização das plantas, tornando desnecessária a utilização deste fitorregulador na produção de mudas de C. saintlegerianum.
Keywords: Orchidaceae; Micropropagation; Plant growth regulators; Acclimatization